The Spread and Development of Psychodrama in Mainland China - Sang, Zhi-qin; Huang, Hao-ming; Benko, Anastasiia; Wu, Yin (Frontiers in Psychology, 2018)
The history of the popularization and research of psychodrama in the west has spanned more than 80 years since it was founded by J. L. Moreno in the 1930s. However, it was only in the 1990s that psychodrama was systematically introduced in mainland China. The historical process of the spread and development of psychodrama in China is complex; therefore, this study approached it from the perspectives of space and time and theoretical development. Considering four events as the critical time points, the history of psychodrama in China can be divided into four periods from a spatiotemporal perspective: pre-contact period, preparatory period, period of prosperity, and the period of new development. Based on the theoretical classification, three major branches of psychodrama in mainland China are represented by Gong Shu’s Yi Shu psychodrama, Katherine Hudgins’ therapeutic spiral model, and campus psychodrama developed by Chinese psychologists.